1982
DOI: 10.1073/pnas.79.6.2106
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelial cells in relaxation of isolated arteries by bradykinin.

Abstract: Bradykinin elicits relaxation of isolated transverse rings of canine coronary, celiac, superior mesenteric, renal, splenic, pulmonary, gastric, and femoral arteries. After endothelial cells of the vessel wall are removed by rubbing of the intimal surface, canine arteries fail to relax upon addition of bradykinin. The endothelium-dependentrelaxation ofcanine arteries remains intact after treatment with cyclooxygenase inhibitors (indomethacin and flurbiprofen), and this argues against mediation by prostaglandins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
167
0
17

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(192 citation statements)
references
References 7 publications
8
167
0
17
Order By: Relevance
“…Bradykinin is able to elicit an endotheliumdependent relaxation of a large variety of canine arteries (Chand & Altura, 1981;Cherry et al, 1982). Such a bradykinin-induced relaxation was also found to occur in pig aorta (Gordon & Martin, 1983), in bovine intrapulmonary artery and vein (Gruetter & Lemke, 1986a) and in bovine coronary artery (Angus et al, 1986b).…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin is able to elicit an endotheliumdependent relaxation of a large variety of canine arteries (Chand & Altura, 1981;Cherry et al, 1982). Such a bradykinin-induced relaxation was also found to occur in pig aorta (Gordon & Martin, 1983), in bovine intrapulmonary artery and vein (Gruetter & Lemke, 1986a) and in bovine coronary artery (Angus et al, 1986b).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown preservation of normal tissue oxygenation in the placental labyrinth even during severe systemic hypoxia and provide evidence for hypoxia-induced activation of NOS being responsible for tissue protection. NOS catalyzes the production of NO that represents a potent vasodilator (9,19). In mammals, three NOS isoforms have been identified: neuronal NOS, iNOS, and eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, three NOS isoforms have been identified: neuronal NOS, iNOS, and eNOS. Whereas iNOS expression is induced by cytokines, hypoxia, and other agents (20,32), eNOS is constitutively expressed but is known to be activated by physical and metabolic stimuli such as shear stress and hypoxia as well (6,9,35). Indeed, it was recently shown that the eNOS promoter contains a hypoxia response element and thus might be a HIF target gene (11).…”
Section: Discussionmentioning
confidence: 99%
“…Among these were the calcium ionophore A23187, substance P and other tachykinins, ATP and ADP, and bradykinin. The work on bradykinin, which was found to be an endothelium-dependent vasodilator of dog and human arteries but not rabbit and cat arteries (which it relaxed by stimulating the release of prostacyclin even in the absence of endothelium), was part of Peter Cherry' s PhD thesis research, and in the published report (27) on this work, the term endothelium-derived relaxing factor, along with the abbreviation EDRF, was first used.…”
Section: Endothelium-dependent Relaxation Edrf and Ni Tric Oxi�ementioning
confidence: 99%